Exploration of Diglossia in Ambon Languages: Social Dynamics and Language Change in Ferguson Perspective: Social Dynamics and Language Change in Ferguson's Perspective - Asbarin, (Linguistik, Terjemahan, Sastra (LINGTERSA), 2025)
This study explores social dynamics and language transformation through the phenomenon of diglossia in Ambon language based on the perspective of Charles A. Ferguson. Diglossia in Ambon is the result of complex interactions between Indonesian and Ambon, which are influenced by social changes and shifts in the context of language use. This study focuses on the analysis of four main aspects of diglossia, namely functional, grammatical, lexicon, and phonology, in order to understand how language variations develop in various communication situations. Research data was collected through observation, documentation, and interviews with IAIN Ambon students. The results of the analysis show that the phenomenon of diglossia in Ambon language occurs due to the mixing of Indonesian as a prestige language with Ambon language which is more used in informal interactions. The shift in the situation from the formal to the informal realm contributes to changes in the structure of the language, both in terms of grammar, vocabulary choices, and phonological patterns used by speakers. The findings of this study confirm that social dynamics have a significant role in shaping patterns of language use in society, reflecting how language adapts to evolving social and cultural contexts. This study not only provides new insights in sociolinguistic studies, but also enriches the understanding of the development of regional languages in Indonesia in the context of bilingualism and diglossia.